The infected and the affected: A longitudinal study of the impact of the COVID-19 pandemic on schoolchildren in Florida - McKune, Sarah L.; Acosta, Daniel; Fujii, Yui; Joyce-Beaulieu, Diana; Sayeed, Md Abu; Cato, Emilee; Flaherty, Katelyn E.; Creasy-Marrazzo, Ashton; Pu, Ruiyu; Kariyawasam, Subhashinie; Arukha, Anantha; Cummings, Derek A. T.; et al. (Frontiers in Public Health, 2023)
Abstract Objectives: To identify risk factors associated with symptoms of anxiety, depression, and obsessive-compulsive disorder (OCD) among children during the first year of the COVID-19 pandemic. Methods: A longitudinal study with three cross-sectional timepoints (April 2020 (n=273), October 2020 (n=180), and April 2021 (n=116)) was conducted at a K-12 public school in Florida. Infection and sero-positivity for SARS-CoV-2 was determined by molecular and serologic approaches. Adjusted odds ratios using mixed effect logistic regression models for symptom-derived indicators of anxiety, depression, and OCD in children in April 2021 are presented; past infection and seropositivity were included in the models. Results: The prevalence of anxiety, depression, or OCD moved from 47.1%, to 57.2%, to 42.2% across the three timepoints during the study. By endline of the study, in April 2021, non-white children were at higher risk for depression and OCD. Risk for anxiety, depression, and OCD was associated with students who lost a family member due to COVID-19 and who were identified as at-risk in previous timepoints. Rates of SARS-CoV-2 infection and seropositivity were low and not statistically associated with assessed outcomes. Conclusions: In situations like the COVID-19 pandemic, targeted mental health interventions and screenings are needed in children and adolescents, especially among minority children.